Optimization of nanocrystalline cellulose particle size using one-factor-at-a-time method under different acid hydrolysis parameters - Abdul Talib, Rosnita; Abdan, Khalina; Chu, Yong soon; Carine, Shu shien lim; Yonchen, Harianto; Chen, Wai Wong; Eric Wei, Chiang Chan (Silpakorn University, 2023)
This study explores the production of nanocrystalline cellulose (NCC) from corn cob (Zea mays), aiming to overcome the challenges of carbonization and reduced yield typically associated with the use of highly concentrated and corrosive sulfuric acid. A systematic approach was adopted employing one-factor-at-a-time analysis to optimize the hydrolysis process, focusing on three key parameters: sulfuric acid concentration, hydrolysis temperature, and duration. The determination of optimized conditions was based on the desired particle size of the NCC produced and the absence of carbonization. The produced NCC was thoroughly characterized using Fourier transform infrared spectroscopy to determine its chemical structure, X-r ay diffraction for crystallinity, and thermogravimetric analysis (TGA) for thermal properties. The results highlighted that the optimal conditions for NCC production involve a sulfuric acid concentration of 40 wt% at a temperature of 70 °C, with a hydrolysis duration of 150 min. These conditions yielded NCC with a uniform particle size of 225.07 nm, no signs of carbonization, and a significantly lower inorganic content at 6.73 w/w% after heating to 590 °C in the TGA. This study thereby offers valuable insights for producing NCC with reduced carbonization and increased yield.